Evaluation of Public Transport Trips Using Mobile Communications. (2016) - Gheorghiu, Răzvan Andrei; Surugiu, Maria Claudia
Abstract: Public transport is the key to future urban sustainable growth and, thus, it must be properly designed and permanently reconfigured to meet the continuously changing demand in modern cities. In order to properly respond to population transport needs, is essential to get information about the trips that are performed in the city and to assess the public transport's performance and ability to transport people according to their needs. The goal of this paper is to propose a method to gather the necessary information using ITS based on mobile communications. The problem addressed in this article refers to the necessity of having permanently updated information about public transport trips in order for the public transport companies to be able to provide a good service that is able to attract more people. This is why we have considered that the implementation of a system able to get (anonymous) data about the people using public transport vehicles would be able to provide a trips map that may be used to improve the service and, thus, to make it more attractive.